DAMPAK ABRASI TERHADAP KONDISI SOSIAL-EKONOMI PEDAGANG DI PANTAI KECAMATAN PALOH KABUPATEN SAMBAS - Doni Rinaldi; Aji Ali Akbar; Jumiati (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2023)
Abrasion has an impact on physical conditions but also affects the socio-economic. This study aims to determine changes in the coastline and socio-economic of traders due to abrasion in Paloh District, Sambas Regency. The location of this research is in three villages, namely Kalimantan Village, Matang Danau Village, and Tanah Hitam Village which located on Paloh District, Sambas Regency. The results show that changes of coastline on the coast of Kalimantan Village, Matang Danau Village and Tanah Hitam Village over a period of 30 years (1990-2020) have experienced abrasion and accretion. The distance of the shoreline shift towards land (abrasion) is 60.58 m with an average rate of change of 2 m/yr, while the shift towards the sea (acretion) is 10.95 m with an average rate of change of 0 .16-0.56 m/yr along 11,884 km of coastline. The impact of the construction of the abrasion-resistant embankment affects the socio-economic conditions of traders, which are in the moderate category.